2020
DOI: 10.1002/cre2.379
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and antibacterial activity of Berberis vulgaris (barberry) against bacteria associated with caries

Abstract: Objectives: The aim of this in-vitro study was to determine the antimicrobial capacity of a Berberis vulgaris plant extract on the bacteria being associated with caries including, Streptococcus mutans, S. sobrinus, S. sanguinis, S. salivaris and Lactobacillus rhamnosus.Material and methods: Chlorhexidine 2% (CHX) mouthwash and ampicillin (10 μg/ disk) were applied as positive control groups. Inhibition zone, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) related to stem, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…For chitosan decoded with CuO/TiO 2 , the CH 2 bending vibration was observed at 1449 cm −1 [ 35 ]. The peak C-O stretching of the berbamine characteristics was measured at 1060 cm −1 [ 32 ]. Cu-Ti-O has a metal-oxygen stretching vibration of 707, 587, and 528 cm −1 [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For chitosan decoded with CuO/TiO 2 , the CH 2 bending vibration was observed at 1449 cm −1 [ 35 ]. The peak C-O stretching of the berbamine characteristics was measured at 1060 cm −1 [ 32 ]. Cu-Ti-O has a metal-oxygen stretching vibration of 707, 587, and 528 cm −1 [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial potential of a Berberis vulgaris plant extract against microorganisms linked with caries, such as Streptococcus spp. and Lactobacillus rhamnosus, was determined in several in vitro studies [ 32 ]. These nanoparticles and phytocompounds are powerful antibacterial and anticancer agents on their own; however, combining them with the natural polymer chitosan could result in a new hybrid treatment strategy that delivers better results and overcomes individual flaws.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the compounds obtained from the alcoholic extract of the flower buds of Dianthus caryophyllus, the extract showed antibacterial activities against the pathogenic bacteria E. coli and S. aureus (25). The compound 1,1,1,5,7,7,7-Heptamethyl-3,3bis(trimethylsiloxy)tetrasiloxane is among the compounds present in the extract of the stem and fruits of Berberis vulgaris, which showed antibacterial activities against caries-causing bacteria (27). 3-Trimethylsilyloxystearic acid is among the compounds present in the methanolic extract of Orobanche crenata, the extract showed strong antioxidant properties and inhibition of the spread of human hepatocellular carcinoma (HepG2), human prostate cancer (PC3), human breast cancer (MCF-7), and human colon carcinoma (HCT-116) (19).…”
Section: Effects Of Endophytic Fungal Filtrates On the Growth Of Some...mentioning
confidence: 99%
“…Recently, Arkadiusz Dziedzic et al ( 16 ) found that berberine can effectively inhibit the growth of S. mutans in vitro . Maryam Kazemipoor et al ( 22 ) reported that barberry plant extract and CHX (chlorhexidine) have similar antimicrobial activity against S. mutans . However, in our knowledge, the antibiofilm effect of berberine on S. mutans has received little or no attention.…”
Section: Introductionmentioning
confidence: 99%